2007
DOI: 10.1007/s10802-007-9170-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Functioning in AD/HD, Predominantly Inattentive and Combined Subtypes

Abstract: In the above-mentioned article there is an apostrophe in the middle of Sabrina's name that should not be there. Her name should read as follows: Sabrina Pope-Boyd. In addition to the above, the following two errors occurred in the abstract: (1) Top second column-should read: "and tasks assessing the impact on reaction time OF varying... ("OF " was omitted)" (2) Last line of abstract-"neurological" should be replaced by "neuropsychological".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
0
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 0 publications
9
44
0
11
Order By: Relevance
“…In our opinion, the patients with ADHD combined presents difficulties with the two systems, "arousal" and "activation" and this can be understood by the difficulty in separating the subtypes of ADHD predominantly inattentive and combined, what was also observed by others authors [20][21][22] .…”
Section: Discussionsupporting
confidence: 61%
“…In our opinion, the patients with ADHD combined presents difficulties with the two systems, "arousal" and "activation" and this can be understood by the difficulty in separating the subtypes of ADHD predominantly inattentive and combined, what was also observed by others authors [20][21][22] .…”
Section: Discussionsupporting
confidence: 61%
“…Fourth, like others [Martel et al, 2007], we have used a total symptom score for ADHD. Some studies find that the inattentive, hyperactive and impulsive subtypes may show different neurocognitive profiles [Nigg, 2005;Solanto et al, 2007]. Thus, a research design examining simultaneously CD and ADHD subtypes in clinical samples may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review concluded that, on the basis of existing data, one of the most robust motivational markers in ADHD was a preference for smaller sooner (SS) over larger later (LL) rewards (Luman, Oosterlaan, & Sergeant, 2005). This pattern of choice has been shown in most (e.g., Antrop et al, 2006;Bitsakou, Psychogiou, Thompson, & Sonuga-Barke, 2009;Dalen, SonugaBarke, & Remington, 2004;Hoerger & Mace, 2006;Kuntsi, Oosterlaan, & Stevenson, 2001;Schweitzer & Sulzer-Azaroff, 1995;Solanto et al, 2001;Sonuga-Barke, Taylor, Sembi, & Smith, 1992), but not all (Bidwell, Willcutt, DeFries, & Pennington, 2007;Scheres et al, 2006;Solanto et al, 2007) studies of ADHD using SS versus LL choice paradigms. A recent meta-analysis reported a pooled effect size for case-control differences of a similar magnitude to those seen for executive function measures .…”
mentioning
confidence: 99%